Entomopathogenic fungi for biological control of Chagas disease vector Rhodnius prolixus - Garcia, Aline Rafaela Moura (2013)
Parasites transmitted by insects are major problems in public health. Conventional methods of control, chemical insecticides, are not sustainable for long periods, generate strong selection pressure on insect populations, for resistance, and can cause damage to the environment and human health. Entomopathogenic fungi have potential for control and management of diseases by insect vectors. In this sense, the objective of this study was to evaluate the pathogenicity of Metarhizium anisopliae and Beauveria bassiana to Rhodnius prolixus (Reduviidae) and the possibility of using these pathogens for the management of Chagas disease. For this, we conducted three preliminary tests in laboratory to: i) assess the pathogenicity and choose infective isolate against triatomines, ii) investigate the virulence of isolates by assaying concentration on mortality and iii) to evaluate the effect of temperature on insects infected with fungus. Through these trials, we observed that isolates of M. anisopliae were more virulent to nymphs of R. prolixus than isolates of B. bassiana, even at low spore concentration. We also observed that the longevity of nymphs infected with the isolate URPE-11 and ENT- 1, M. anisopliae and B. bassiana, respectively, was reduced with increasing temperature. However, ENT-1 showed to be more effective than URPE-11 both at high and low temperatures. In the field, isolates able to infect the host in adverse temperature conditions are preferable, however, other aspects of these isolates must be evaluated to confirm the possibility of using them for control and management of vectors of Chagas disease.